SERBIAN ETHNIC STRATUM IN THE MODERN REPUBLIC OF NORTH MACEDONIA (TERRITORY OF OLD SERBIA AND MACEDONIA) - Pejin, Jovan (Political Review, 2023)
The paper presents a historical cross-section of social, military, ethnic, and political conditions in Southeastern Europe, i.e. Balkans, more precisely in the area of Old Serbia and Macedonia, parts of today’s Bulgaria, Turkey and neighboring areas. The historical course of a long duration was followed, from the pre-Nemanjic period to the Balkan wars of 1912/1913. years. Special attention is given to the Serbian ethnic group in the area of Old Serbia and Macedonia, which today covers the territory of North Macedonia. The paper lists the main historical events that connect the Serbs and their state with this area, and it primarily mentions the Serbian people, i.e. the Serbian ethnic stratum, as well as important events that speak of the history of Serbian statehood, such as the fact that the Serbian king Milutin chose Skopje as the Serbian capital, and Dušan was crowned Serbian emperor in Skopje (1346). Special attention is devoted to the depiction of the struggle between Serbs and Bulgarians who, after receiving the Exarchate (1870), worked intensively on the Bulgarianization of these Serbian areas with the use of terror, violence and murders of prominent Serbian priests and individuals from Serbian society.